The composition of ileostomy fluid. Issue 4 (December 1963) - Kanaghinis, T.; Lubran, M.; Coghill, N. F.
Abstract : The paper presents data on the sodium, potassium, and water content of ileostomy dejecta from 12 patients with new ileostomies and six patients with established ones. The effects of administration of electrolytes and codeine on these parameters are described. The literature on the chemistry of ileostomy is critically reviewed.